Streamlined In Vivo Selection and Screening of Human Prostate Carcinoma Avid Phage Particles for Development of Peptide Based In Vivo Tumor Imaging Agents - R. Newton-Northup, Jessica; D. Figueroa, Said; L. Deutscher, Susan (Combinatorial Chemistry & High Throughput Screening, 2011)
Bacteriophage (phage) display has been exploited for the purpose of discovering new cancer specific targeting peptides. However, this approach has resulted in only a small number of tumor targeting peptides useful as in vivo imaging agents. We hypothesize that in vivo screening for tumor uptake of fluorescently tagged phage particles displaying multiple copies of an in vivo selected tumor targeting peptide will expedite the development of peptide based imaging agents. In this study, both in vivo selection and in vivo screening of phage displaying foreign peptides were utilized to best predict peptides with the pharmacokinetic properties necessary for translation into efficacious in vivo imaging agents. An in vivo selection of phage display libraries was performed in SCID mice bearing human PC-3 prostate carcinoma tumors. Eight randomly selected phage clones and four control phage clones were fluorescently labeled with AlexaFluor 680 for subsequent in vivo screening and analyses. The corresponding peptides of six of these phage clones were tested as 111Inlabeled peptide conjugates for single photon emission computed tomography (SPECT) imaging of PC-3 prostate carcinomas. Two peptide sequences, G1 and H5, were successful as in vivo imaging agents. The affinities of G1 and H5 peptides for cultured PC-3 cells were then analyzed via cell flow cytometry resulting in Kd values of 1.8 μM and 2.2 μM, respectively. The peptides bound preferentially to prostate tumor cell lines compared to that of other carcinoma and normal cell lines, and H5 appeared to possess cytotoxic properties. This study demonstrates the value of in vivo screening of fluorescently labeled phage for the prediction of the efficacy of the corresponding 111In-labeled synthetic peptide as an in vivo SPECT tumor imaging agent.
Keywords: FACScan analysis